Diagnostic biosignature transformation under simulated martian radiation in organic-rich sedimentary rocks - Roussel, A.; McAdam, A. C.; Graham, H. V.; Pavlov, A. A.; Achilles, C. N.; Knudson, C. A.; Steele, A.; Foustoukos, D. I.; Johnson, S. S. (Frontiers in Astronomy and Space Sciences, 2022)
As we look for traces of ancient life on Mars, we need to consider the impact of ionizing radiation in the biosignature preservation process. Here, we irradiated two organic rich terrestrial samples (Enspel and Messel shales) that have Martian analog mineralogies, with simulated cosmic rays to a dose of 0.9MGy, equivalent of 15 million years of radiation exposure on the Martian surface. We compared a range of biosignatures before and after exposure, including total organic carbon, bulk stable carbon isotope ratios, diagnostic lipid biomarkers (hopanes and steranes), and Raman signatures akin to those collected by the Scanning Habitable Environments with Raman and Luminescence for Organics and Chemicals (SHERLOC) instrument on Perseverance. While we did not observe a significant difference in total organic carbon, bulk stable carbon isotopes, or Raman G-band signatures, we found that five lipid biomarkers decreased by a factor of two to three in the Enspel shale. This degree of degradation exceeds current predictions by existing models or experimental studies in organic rich samples and challenges our current understanding of complex biosignatures under ionizing irradiation.